Euro Crash : How Asset Price Inflation Destroys the Wealth of Nations - Brown, Brendan; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Euro Crash is a unique analysis of the European Monetary Union, arguing that it was not sub-optimal currency areas or profligate government spending but instead fatal flaws in monetary design and an appalling series of policy mistakes by the European Central Bank that lead to the current and ongoing Eurozone crisis.
Keywords: Science; Science; Science, general